The Prevalence of Herpes Virus Infections in the Active Phase in Hospitalized Children with Rotavirus Infection - V. V. Krasnov; T. D. Aleksandrova; N. E. Senyaginа; L. V. Nazarova (LLC "Diagnostics and Vaccines", 2018)
Under the supervision there were 301 children hospitalized in an infectious hospital with a diagnosis of rotavirus infection. All children were examined for the presence of human herpes virus DNA 4, 5 and type 6 (EBV, CMV, HHV6) in the blood. The majority of hospitalized children with rotavirus infection were under 3 years of age (85.7%). Revealed a high percentage of children of different ages with herpes viral infections in the active phase. In the case of monoinfection, the most frequent active infection was caused by HHV6 type (45.5%). In the case of an associated infectious process, the predominant viruses were EBV and HHV6 (29.3%). Children with active herpes virus who had a rotavirus infection need follow-up monitoring.